Correction: Association between sanitary toilets and health poverty vulnerability among rural western Chinese adults aged 45 years and older: A cross-sectional study. - PLOS ONE Editors (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0308688.].